The influences of new modality of experiential marketing with the development of virtual platform: A study on Asiatic Experiential Marketing Ltd - Sabbir, Rayhan (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.